2021
DOI: 10.21203/rs.3.rs-475149/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic architecture of smoking: Evaluating rare variant contribution from deep whole-genome sequencing of up to 26,000 individuals

Abstract: Background Across complex traits, common variants explain only a modest amount of variance, with SNP-heritability consistently below heritability estimates from close relatives. Here, we examined the contribution of rare variant to tobacco use risk in up to 26,000 individuals of European ancestry in the Trans-Omics for Precision Medicine (TOPMed) program with whole genome sequence (WGS;~30X coverage).Method We grouped about 35 million genetic variants by their minor allele frequencies (MAF) and linkage disequi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Such studies have significantly improved our understanding of the polygenic architecture of smoking phenotypes and pointed to genes and pathways underlying smoking behavior, including genes encoding nAChRs, genes involved in nicotine metabolism and dopaminergic and glutamatergic signaling 15 . However, to date, few studies based on whole exome or genome sequencing data have been reported 19,50 and such studies were conducted in sample sizes insufficient to capture associations at variant and gene level resolutions. Hence, our understanding of the contributions of rare variants to smoking behavior has been minimal so far.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have significantly improved our understanding of the polygenic architecture of smoking phenotypes and pointed to genes and pathways underlying smoking behavior, including genes encoding nAChRs, genes involved in nicotine metabolism and dopaminergic and glutamatergic signaling 15 . However, to date, few studies based on whole exome or genome sequencing data have been reported 19,50 and such studies were conducted in sample sizes insufficient to capture associations at variant and gene level resolutions. Hence, our understanding of the contributions of rare variants to smoking behavior has been minimal so far.…”
Section: Discussionmentioning
confidence: 99%